Methods for Baiting and Enriching Fungus-Feeding (Mycophagous) Rhizosphere Bacteria - Ballhausen, Max-Bernhard; van Veen, Johannes A.; Hundscheid, Maria P. J.; de Boer, Wietse (Frontiers in Microbiology, 2015)
Mycophagous soil bacteria are able to obtain nutrients from living fungal hyphae. However, with exception of the soil bacterial genus Collimonas, occurrence of this feeding strategy has not been well examined. Evaluation of the importance of mycophagy in soil bacterial communities requires targeted isolation methods. In this study, we compared two different approaches to obtain mycophagous bacteria from rhizospheric soil. A short-term method based on baiting for bacteria that can rapidly adhere to fungal hyphae and a long-term method based on the enrichment of bacteria on fungal hyphae via repeated transfer. Hyphae-adhering bacteria were isolated, identified by 16S rDNA sequencing and tested for antifungal activity and the ability to feed on fungi as the sole source of carbon. Both methods yielded a range of potentially mycophagous bacterial isolates with little phylogenetic overlap. We also found indications for feeding preferences among the potentially mycophagous bacteria. Our results indicate that mycophagy could be an important growth strategy for rhizosphere bacteria. To our surprise, we found several potential plant pathogenic bacteria among the mycophagous isolates. We discuss the possible benefits that these bacteria might gain from colonizing fungal hyphae.